Use of propolis for skin wound healing: systematic review and meta-analysis - Machado Velho, Julia Carnelós [UNESP]; França, Thais Amaral [UNESP]; Malagutti-Ferreira, Maria José [UNESP]; Albuquerque, Edilson Rodrigues; Lívero, Francislaine Aparecida dos Reis; Soares, Murilo Racy; Soares, Ademilson Espencer Egea; Ribeiro-Paes, João Tadeu [UNESP] (Springer Nature, 2023)
Propolis is a natural resin that is produced by bees. It has anti-inflammatory and antibiotic properties, promotes reepithelization, and stimulates skin regeneration. Propolis has great potential for the development of new therapeutic approaches to treat skin ulcers. The present study performed a systematic review and meta-analysis of published studies of the use of propolis for the regeneration of cutaneous wounds and its efficacy as a therapeutic agent. Data were collected from articles in the PubMed, SCOPUS, and Web of Science databases that were published since 1900 by searching the terms “propolis” AND “wound healing.” This search yielded 633 articles, of which 43 were included in this systematic review and meta-analysis. The results showed that interest in the therapeutic efficacy of propolis has increased over the years. The studies reported that the propolis was effective for the treatment of skin ulcers by promoting a higher percentage of healing than classically employed interventions. The mode of propolis application has also evolved. An increasing number of studies combined it with other substances and materials to achieve additive or synergistic effects on the skin regeneration process. Propolis appears to be an effective therapeutic alternative for the treatment of skin ulcers.
Keywords: Alternative therapy; Dressings; Natural products; Skin wounds; Wound regeneration